2009
DOI: 10.1002/adsc.200900610
|View full text |Cite
|
Sign up to set email alerts
|

A Novel NADH Model: Design, Synthesis, and its Chiral Reduction and Fluorescent Emission

Abstract: A novel chiral nicotinamide adenine dinucleotide hydrogen (NADH) model with C 3 symmetry was designed and synthesized. Hydrogens at the C-4 position of all dihydropyridine rings in the inner part of the bowl could transfer to the substrate with powerful enantioselectivity. This novel C 3 symmetrical NADH model is capable of fluorescence emission at 455 nm when excited at 390 nm.Keywords: chiral NADH model; enantioselectivity; fluorescence; magnesium(II); synthesis The coenzyme nicotinamide adenine dinucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…2 Over the years, numerous NADH mimics have been synthesized by organic chemists for use as enantioselective reducing agents in the laboratory. [7][8][9][10][11][12][13] Recently, this reaction was also used to characterize more unconventional enantioselective catalysts, including heterogeneous platinum-supported 14 and nano-confined 15 catalysts. [7][8][9][10][11][12][13] Recently, this reaction was also used to characterize more unconventional enantioselective catalysts, including heterogeneous platinum-supported 14 and nano-confined 15 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…2 Over the years, numerous NADH mimics have been synthesized by organic chemists for use as enantioselective reducing agents in the laboratory. [7][8][9][10][11][12][13] Recently, this reaction was also used to characterize more unconventional enantioselective catalysts, including heterogeneous platinum-supported 14 and nano-confined 15 catalysts. [7][8][9][10][11][12][13] Recently, this reaction was also used to characterize more unconventional enantioselective catalysts, including heterogeneous platinum-supported 14 and nano-confined 15 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…2) When treated with thioureas, these two functional groups may undergo double functional group transformations to become the thiazole compounds 5 by the Hantzsch reaction. [7] Thus, we envisioned that the chemical transformation of the a-bromoketone to thiazole structure should inhibit both the fluorescence quenching processes and, thus, restore the intense fluorescence of the coumarin dye. In other words, we should observe a pronounced fluorescence turn-on signal, if probe 1 can be converted to thiazole compounds 5 by thioureas.…”
mentioning
confidence: 99%
“…3 ) Chiral NADH models with C 3 -symmetry. In our previous work, we have designed and synthesized the first C 3 symmetrical NADH model compound 4 with a special bowl-shaped conformation 18 .…”
mentioning
confidence: 99%
“…Therefore, to design novel NADH models with symmetric structure and excellent enantioselectivity is a challenge for chemists. For the C 3 -symmetry models, it was shown that the three identical dihydropyridine units were connected to form a rigidly defined concave cavity which could encase and fix certain substrates to accomplish the biomimetic reduction with high yields and enantioselectivity 18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation